Unformatted text preview: 28 Economic Dynamics
Consider (iii) above. This is an autonomous ﬁrst-order homogeneous differential
equation. Rearranging the equation we have
Integrating both sides with respect to t yields
dt x k dt ln x(t) = kt + c0
where c0 is the constant of integration. Taking exponentials of both sides yields
x(t) = cekt
where c = ec0 . It is readily veriﬁed that this is indeed a solution by differentiating
it and substituting. Thus
kcekt = kx = kcekt
which holds identically for any a < t < b.
To check whether x(t) = 1 + t + cet is a solution of dx/dt = x − t, we can differentiate x with respect to t and check whether the differential equation holds exactly.
= 1 + cet
... 1 + cet = 1 + t + cet − t
Hence x(t) = 1 + t + cet is indeed a solution.
p(t) = ap0
bp0 + (a − bp0 )e−at is a solution to the differential equation
= p(a − bp)
Differentiating the solution function with respect to t we obtain
= −ap0 [bp0 + (a − bp0 )e−at ]−2 (−a(a − bp0 )e−at )
a2 p0 (a − bp0 )e−at
[bp0 + (a − bp0 )e−at ]2 ...
View Full Document